Defective Interfering Particles of Poliovirus IV. Mechanisms of Enrichment - Cole, Charles N. (1973)
Infection of HeLa cells by mixtures of standard poliovirus and defective, interfering (DI) poliovirus particles leads to a higher ratio of DI particles in the progeny than in the inoculum. The extent of this enrichment could be varied by various manipulations of the co-infected cells. At any time during the infection cycle, virions made within short times after addition of radioactive uridine were hyperenriched in DI particles; this transient hyperenrichment fell to the equilibrium enrichment level within 45 min after uridine addition. A shift of the temperature of infection from 37 to 31 C also led to a hyperenrichment of DI particles and pulse-labeling revealed a superimposed transient hyperenrichment. By contrast, cells continuously infected at 31 C showed a severe decrement in DI particles apparently because poliovirus DI particles behave as cold-sensitive mutants for RNA synthesis. Cycloheximide treatment early in the infection cycle also led to hyperenrichment. Study of the cycloheximide effect showed that the drug acted as if to change the input ratio of standard to DI particles. These effects on enrichment can be explained as aspects of two different phenomena: enrichment due to preferential DI RNA synthesis and enrichment due to preferential encapsidation of DI RNA. Both mechanisms probably play a role in the normal level of enrichment.